The Two-machine Flow-shop Scheduling Problem with a Single Server and Unit Server Times - Ling, Shi; Guang, Cheng Xue (Journal of Informatics and Mathematical Sciences, 2012)
We consider the problem of two-machine flow-shop scheduling with a single server and unit server times, we show that this problem is NP-hard in the strong sense and present a simple greedy algorithm for it with worst-case bound $\frac{3}{2}$.